Preaching Messages We Never Intended: LGBTIQ-based Microaggressions in Classroom and Pulpit - Sanders, Cody J. (Theology & sexuality, 2013)
Churches and denominations are increasingly practicing welcome and affirmation of lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ) people and many seminaries and divinity schools now incorporate training on LGBTIQ competency into the curriculum. Yet, amid increasingly overt affirmation, there are subtler ways of bringing to expression the long history of Christian LGBTIQ negativity that are unintentional and often go unnoticed and unchallenged in institutional contexts. This article introduces the social scientific concept of “microaggressions” as a necessary component of training for religious professionals intending to work with and alongside LGBTIQ persons. The article will suggest that in the context of preaching, microaggressions—brief, unintended, and often-unconscious expressions of LGBTIQ denigration — should be examined as a part of the curriculum in homiletics classrooms. What can be learned about microaggressions in the classrooms can serve as a parallel for continued examination of the subtly aggressive speech acts that are perpetrated against LGBTIQ people as “unofficial” messages of denigration, often in self-identified “welcoming” schools and congregations.